(untitled) (SCIENCE TIME JOURNAL, 2025)
This article focuses on teaching students etiquette through hadiths and developing their general cultural competencies. In the “Tarbiya” lesson, a number of general requirements for selecting hadiths for the specified topics are highlighted. In the history of our people, many types of live upbringing were used in the upbringing of children in childhood and adolescence, and the meaning of live upbringing is highlighted.